Cupriavidus B-7 immobilized biochar: an effective solution for Cd accumulation alleviation and growth promotion in pakchoi (Brassica Chinensis L.) - Sun, Yefang; Ouyang, Da; Cai, Yiming; Guo, Ting; Li, Mei; Zhao, Xinlin; Zhang, Qichun; Chen, Ruihuan; Li, Fangzhen; Wen, Xiujuan; Xie, Lu; Zhang, Haibo (Biochar (Online), 2024)
Cd contamination, especially in farmland soil, can pose serious threats to human health as well as ecological security. Stabilization is an important strategy for agricultural soil Cd remediation. In this study, a Cd-resistant strain ( Cupriavidus B-7) was isolated and loaded onto cow manure (CDB), rice straw (RSB) and pine wood biochar (PB) to investigate its effects on Cd stabilization by a 60-day pot experiment. Results indicated that the Cupriavidus B-7-loaded biochar (labelled as CDBB, PBB and RSBB) reduced the CaCl 2 -extractable Cd by 43.06–59.78%, which was significantly superior to individual applications of Cupriavidus B-7 and biochar. Likewise, the soil physicochemical properties, urease, catalase and phosphatase activities were improved, indicating improved soil health. Consequently, dry weights of pakchoi’s shoot and root were increased by 938.9–1230.9% and 149.1–281.2%, respectively, by applying CDBB, PBB and RSBB. Meanwhile, the Cd accumulation in pakchoi shoots decreased by 38.06–50.75%. Notably, the RSBB exhibited an optimal performance on pakchoi growth promotion and Cd accumulation alleviation. The structural equation model indicated the synergistic effect on pakchoi growth promotion and Cd accumulation decreased between biochar and Cupriavidus B-7. Our research provides some new insights into the development of strategies for green and sustainable remediation of Cd-contaminated soil. Graphical Abstract Highlights A Cd resistant Cupriavidus B-7 (B-7) was isolated from copper mining soil Biochar, B-7 and their conbination were used to remediate Cd polluted soil Biochar loaded B-7 outperformed individual treatments for Cd stabilization Biochar loaded B-7 alleivated the Cd uptake and promoted pakchoi growth